Survey of Physical Functioning and Prevalence of Chronic Illnesses Among the Elderly People - Aghil Habibi; Mohammad Taghi Savadpoor; Behnam Molaei; Mahmod Samshiri; Mostafa Ghorbani (Sālmand, 2009)
Objectives: The purpose of this study was to determine the OF physical functioning level and prevalence of chronic illness among elderlypeople in west region of Tehran.